Svarthamaren seabirds, sentinels of the Southern Ocean - Descamps, Sébastien; Moreau, Sébastien; Tarroux, Arnaud; Lorensten, Svein-Håkon; Bustnes, Jan-Ove; Yoccoz, Nigel G; Borgå, Katrine; Carravieri, Alice; Patrick, Samantha (Fram forum, 2021)
Keywords: Sørishavet; forurensning; klimaendringer; marin biologi; marine økosystemer; miljøendringer; observasjoner; ornitologi; sjøfugler; zoologi; økologi

An ocean of possibilities: antarctic petrel's foraging in the Southern Ocean - Tarroux, Arnaud; Fauchald, Per; Varpe, Øystein; Yoccoz, Nigel G; Descamps, Sébastien (Fram forum, 2021)
Keywords: Sørishavet; fôring; marin biologi; observasjoner; ornitologi; petreller; sjøfugler; zoologi

High inter- and intraspecific niche overlap among three sympatrically breeding, closely related seabird species: Generalist foraging as an adaptation to a highly variable environment? - Dehnhard, Nina; Achurch, Helen; Clarke, Judy; Michel, Loïc N; Southwell, Colin; Sumner, Michael D; Eens, Marcel; Emmerson, Louise (Journal of Animal Ecology, 2020)
Ecological niche theory predicts sympatric species to show segregation in their spatio-temporal habitat utilization or diet as a strategy to avoid competition. Similarly, within species individuals may specialize on specific dietary resources or foraging habitats. Such individual specialization seems to occur particularly in environments with predictable resource distribution and limited environmental variability. Still, little is known about how seasonal environmental variability affects segregation of resources within species and between closely related sympatric species. The aim of the study was to investigate the foraging behaviour of three closely related and sympatrically breeding fulmarine petrels (Antarctic petrels Thalassoica antarctica, cape petrels Daption capense and southern fulmars Fulmarus glacialoides) in a seasonally highly variable environment (Prydz Bay, Antarctica) with the aim of assessing inter- and intraspecific overlap in utilized habitat, timing of foraging and diet and to identify foraging habitat preferences. We used GPS loggers with wet/dry sensors to assess spatial habitat utilization over the entire breeding season. Trophic overlap was investigated using stable isotope analysis based on blood, feathers and egg membranes. Foraging locations were identified using wet/dry data recorded by the GPS loggers and expectation-maximization binary clustering. Foraging habitat preferences were modelled using generalized additive models and model cross-validation. During incubation and chick-rearing, the utilization distribution of all three species overlapped significantly and species also overlapped in the timing of foraging during the day—partly during incubation and completely during chick-rearing. Isotopic centroids showed no significant segregation between at least two species for feathers and egg membranes, and among all species during incubation (reflected by blood). Within species, there was no individual specialization in foraging sites or environmental space. Furthermore, no single environmental covariate predicted foraging activity along trip trajectories. Instead, best-explanatory environmental covariates varied within and between individuals even across short temporal scales, reflecting a highly generalist behaviour of birds. Our results may be explained by optimal foraging theory. In the highly productive but spatio-temporally variable Antarctic environment, being a generalist may be key to finding mobile prey—even though this increases the potential for competition within and among sympatric species.
Keywords: Antarktis; biologging; klimaendringer; observasjoner; ornitologi; overvåking; sjøfugler; stabile isotoper; zoologi; økologi; økosystemer

Post-depositional loss of nitrate and chloride in Antarctic snow by photolysis and sublimation: a field investigation - Noro, Kazushi; Takenaka, Norimichi (Polar Research, 2020)
Nitrate in snow is subject to post-depositional processing, which leads to a net loss and redistribution within the snowpack. The relative importance of post-depositional loss processes such as the volatilization of nitric acid (HNO3) and photolysis of nitrate has long been debated. Changes in nitrate and chloride concentrations in the snowpack were investigated at H128 (69°23.584’S, 41°33.712’E), an Antarctic coastal site approximately 100 km from Syowa Station in East Antarctica from December 2015 to February 2016. Results indicate that chloride migrated to deeper sites within the snowpack under the influence of water vapour movement. Moreover, 50% of the nitrate on surface snow was lost to photolysis, and approximately 20% of the nitrate was absent at a depth of 40 cm. To enhance our knowledge of the Antarctic geochemical cycle, this study is the first to suggest chloride ion movement in snowpacks or significant nitrate loss for any Antarctic coastal site.
Keywords: Antarktis; geokjemi; kromatografi; observasjoner; ozon; snø; temperatur

Foraging tactics in dynamic sea-ice habitats affect individual state in a long-ranging seabird - Tarroux, Arnaud; Cherel, Yves; Fauchald, Per; Kato, Akiko; Love, Oliver P; Ropert-Coudert, Yan; Spreen, Gunnar; Varpe, Øystein; Weimerskirch, Henri; Yoccoz, Nigel G; Zahn, Sandrine; Descamps, Sébastien (Functional Ecology, 2020)
Abstract Individual heterogeneity in diet and foraging behaviour is common in wild animal populations, and can be a strong determinant of how populations respond to environmental changes. Within populations, variation in foraging behaviour and the occurrence of individual tactics in relation to resources distribution can help explain differences in individual fitness, and ultimately identify important factors affecting population dynamics. We examined how foraging behaviour and habitat during the breeding period related to the physiological state of a long-ranging seabird adapted to sea ice, the Antarctic petrel Thalassoica antarctica. Firstly, using GPS tracking and state-switching movement modelling (hidden Markov models) on 124 individual birds, we tested for the occurrence of distinct foraging tactics within our study population. Our results highlight a large variation in the movement and foraging behaviour of a very mobile seabird, and delineate distinct foraging tactics along a gradient from foraging in dense pack ice to foraging in open water. Secondly, we investigated the effects of these foraging tactics on individual state at return from a foraging trip. We combined movement data with morphometric and physiological measurements of a suite of plasma metabolites that provided a general picture of a bird's individual state. Foraging in denser sea ice was associated with lower gain in body mass during brooding, as well as lower level of energy acquisition (plasma triacylglycerol) during both brooding and incubation. We found no clear relationship between the foraging tactic in relation to sea ice and the energetic stress (changes in plasma corticosterone), energetic balance (β-hydroxybutyrate) or trophic level (δ15N). However, a shorter foraging range was related to both the energetic balance (positively) and the trophic level (negatively). Our results highlight a diverse range of foraging tactics in relation to sea ice in Antarctic petrels. While the various foraging tactics do not seem to strongly alter energetic balance, they may affect other aspects of Antarctic petrels' physiology. Future changes in sea-ice habitats can thus be expected to have an impact on the individual state of seabirds such as Antarctic petrels, which could ultimately affect their population dynamics. Nonetheless, strong individual heterogeneity in the use of sea-ice habitats by a typical pagophilic species might strengthen its resilience to environmental changes and in particular to forecasted sea-ice loss. A free Plain Language Summary can be found within the Supporting Information of this article.
Keywords: Sørishavet; fôring; havis; marin biologi; miljøendringer; observasjoner; ornitologi; petreller; sjøfugler; sjøis; smelting; zoologi